The role of parenting styles in increasing the achievement of Shorinji Kempo athletes: a literature review - Wali, Carles Nyoman; Yuniana, Rina; Nugroho, Sigit; Pranata, Doni; Talib, Kamal bin (Universitas Negeri Yogyakarta, 2024)
Achievement is one of the universal aspiration among athletes in the world of sports. The aim of this research is to determine the role of parenting styles in enhancing the performance of Shorinji Kempo athletes. The study employs a literature review method with a qualitative approach, using data collection techniques that include editing, organizing, and synthesizing information. The data analysis conducted through content analysis, utilizing internet applications such as Scopus, Sinta, and Google Scholar. The results of this study show parental involvement plays a crucial role in boosting the performance of Shorinji Kempo athletes, particularly during adolescence. Parents are the jewel and main educators for an athlete at home and in the social environment, even though they train with a coach and then study at school. While coaches and teachers contribute to an athlete's development, they act as extensions of parental guidance, providing education and support that may not be available at home. Facilities that cannot be obtained at home but are obtained at school can be complement for children in their development process, while coaches are developers of children's talents and interests that are previously identified by parents. The study concludes that the achievements of young athletes are significantly influenced by the parenting styles they experience. The role of parents in this case is to provide warm, caring, and affectionate family care that has maximum positive impact. As a result, athletes are more likely to grow into well-rounded adults with strong personal qualities, capable of fully realizing their talents and achieving excellence in sports performance.